ALI JUM’AH APPROACH ON QUR’ANIC MAQĀSIDĪ EXEGESIS; A STUDY OF AL-NIBRĀS FĪ TAFSĪR AL-QUR’ĀN - Burhanuddin, Mamat Salamet; Kholida, Noer Diana (Universitas Nurul Jadid, 2021)
This study aims to discuss Maqāsidī exegesis in the tafsir of al-Nibrās fī Tafsīr al-Qur’an al-Karīm by Alī Jum’ah. As a figure on fiqh studies, Alī Jum’ah’s exegesis was born from a very strong maqāsid nuance, mainly related to contemporary legal issues. This article discusses how the epistemology of the maqāsidī exegesis used by Alī Jum’ah in interpreting the Qur’an and how the nuances of the maqāsid play a role in responding to contemporary problems. By using thematic writing techniques on legal verses and using descriptive analysis methods, this research results in the conclusion that the epistemology of maqāsidī which is applied in the book al-Nibrās fī Tafsīr al-Qur’ān al-Karīm prioritizes fiqh analysis and fiqh principles rather than discussion of tafsīr as in general. Through the maqāsidi’s approaches which are based on these principles, Ali Jum’ah tends to study usūl al-Fiqh and maqāsid rather than the interpretation itself. This research also confirms that a person’s scientific background also gives colors and patterns in interpreting the Qur’an